2017
DOI: 10.1021/acsami.7b04982
|View full text |Cite|
|
Sign up to set email alerts
|

Block Copolymer Based Nanoparticles for Theranostic Intervention of Cervical Cancer: Synthesis, Pharmacokinetics, and in Vitro/in Vivo Evaluation in HeLa Xenograft Models

Abstract: Polymer-based nanoparticles have proven to be viable carriers of therapeutic agents. In this study, we have developed nanoparticles (NPs) from polypeptide-polyethylene glycol based triblock and diblock copolymers. The synthesized block copolymers poly(ethylene glycol)-b-poly(glutamic acid)-b-poly(ethylene glycol) (GEG) and poly(ethylene glycol)-b-poly(glutamic acid) (EG) conjugated with folic acid for targeting specificity (EGFA) have been used to encapsulate methotrexate (MTX) to form M-GEG and M-EGFA NPs aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…As with other NP types, several studies have reported the radiolabelling of polymeric micelles with 99m Tc using the direct labelling method. [390][391][392][393][394][395][396][397][398] Once again, this was shown to be a robust technique; with reported RCYs generally being 495% under optimised conditions and serum stability ca. 98% after 24 h. [395][396][397] The radioiodination of polymeric micelles has also been reported.…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 97%
“…As with other NP types, several studies have reported the radiolabelling of polymeric micelles with 99m Tc using the direct labelling method. [390][391][392][393][394][395][396][397][398] Once again, this was shown to be a robust technique; with reported RCYs generally being 495% under optimised conditions and serum stability ca. 98% after 24 h. [395][396][397] The radioiodination of polymeric micelles has also been reported.…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 97%
“…Increasing the survival rates of the treated mice indicate the potent anticancer effect of these polymer NPs. This study proved the availability to use these NPs as a potential theranostic replacement for both chemotherapeutic and diagnostic agent for cervical carcinoma [96].…”
Section: Theranostic Polymer Nanoparticlesmentioning
confidence: 76%
“…Encapsulation of methotrexate (MTX), a chemotherapeutic agent, in polymeric NPs is crucial in controlling its toxicity and side effects. 89 Two different block copolymers (poly(ethylene glycol)-b-poly(glutamic acid)-b-poly(ethylene glycol) (GEG) and poly(ethylene glycol)-bpoly(glutamic acid) (EG) conjugated with FA have been designed and used to encapsulate MTX. Both NPs, named M-GEG and M-EGFA NPs, are employed for passive and active targeting of cervical carcinoma, respectively [see Figure 3a (ii)].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Both NPs, named M-GEG and M-EGFA NPs, are employed for passive and active targeting of cervical carcinoma, respectively [see Figure 3a (ii)]. 89 FA has been used as a homing device to actively target and direct M-EGFA NPs towards the tumor, facilitating targeted drug release at the tumor site. On the other hand, M-GEG NPs passively target and accumulate at the cancer cells, by exploiting the EPR effect.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%